Analisis Koreksi Fiskal Positif dan Koreksi Fiskal Negatif Terhadap Pajak Terhutang Badan Pada PT Federal Internasional Finance - Yayan Yanuari; Budi Rachmawati (Mulia Pratama, 2022)
In calculating the amount of taxable income, the taxpayer must refer to the applicable tax laws. With the applicable tax regulations, the company as a taxpayer must make adjustments or corrections to the financial statements. Corrections occur due to differences in principles, methods, treatment and recognition between Financial Accounting Standards and Fiscal or tax. A positive correction is a correction that causes an increase in taxable profit due to an expense that cannot be recognized on a tax basis and a negative correction is a correction that causes a decrease in taxable profit due to an income that is recognized in accounting but is not recognized fiscally. This thesis aims to (1) find out how much positive fiscal correction affects the corporate tax payable, (2) find out how much negative fiscal correction affects the corporate tax payable and (3) to find out whether positive fiscal correction and negative fiscal correction on the income statement loss is in accordance with tax regulations. The type of is quantitative data, the sample of fiscal income period 2020, the data collection method is library research and field research (observation, documentation, and interviews). The data analysis is quantitative and qualitative. debt agency using a formula or formula and qualitative analysis with a thematic approach using coding in the form of words or text. And the results of the research (1) Positive correction at PT Federal Internasional Indonesia amounting to Rp 371,011,067.00 from commercial profit of Rp 1,640,295,000.00 positive correction has the effect of maximizing fiscal profit by 22.58% and maximizing tax payable by 29.50% . (2) Negative correction at PT Federal Internasional Finance is very high, which is Rp. 1,017,488,000.00 from commercial profit of Rp.1,640,295,000.00 negative correction has an effect of 62.03% on fiscal profit and has an effect of 102% on tax payable which means that this negative correction has a very large effect in minimizing the tax payable. (3) The calculation of the tax payable at PT Federal Internasional Finance is in accordance with the laws and regulations.